Application of Job Safety Analysis (JSA) to Mitigate Ergonomic Risks in Visual Communication Design Vocational High School - Dwi Septiani; Suhendar Suhendar; Irwanto Irwanto (Universitas Negeri Padang, 2025)
This study aimed to identify ergonomic hazards and assess occupational health risk levels among Vocational High School students in the Visual Communication Design program. Using a qualitative approach with 32 Grade XII participants, data were collected through participatory observation of 10 critical work steps and workstation measurements. The analysis, mapped into a Job Safety Analysis (JSA) matrix, revealed significant facility dimensional gaps that forced postural compensation. Results indicated that 60% of work steps were classified as High Risk, with the highest risk scores (R=15) identified in repetitive mouse usage and long-duration static work. These risks were driven by an